Who does this benefit? A consideration of demographics in the access and impact of retirement from college sport programming - Kloetzer, Hannah; Harry, Molly; Taylor, Elizabeth (Journal of Intercollegiate Sport, 2025)
Sport retirement can reveal a host of difficulties for college athletes including minimal career preparation, mental health struggles, and identity foreclosure. While college athletes almost always note the challenges of leaving their sport behind, these challenges can be mitigated through transition programming. However, what types of programming are more useful, and for whom, is understudied. Through a mixed method survey, this study explored differences in access and impact of retirement from sport programming based on athletes’ (n = 707) demographic differences (e.g., race, division), through the lens of Goodman and colleagues’ (2006) three phases of transition. Findings revealed that Black athletes and those from working class backgrounds found programs to be more impactful than other demographic groups, supporting the argument for personalized retirement support. Additionally, Division II athletes not only had the greatest access to retirement programming, but also found programming to have more impact than other divisions. However, athletes noted that more programs are needed for every division.